2012
DOI: 10.1021/ef2018989
|View full text |Cite
|
Sign up to set email alerts
|

Wax Deposition in Stratified Oil/Water Flow

Abstract: While diffusion as the major mechanism for wax deposition has been investigated in past decades, wax gelation has mostly been studied in quiescent conditions and is considered to be less significant than diffusion in flow conditions. In this study, gelation has been observed as a major mechanism for the formation of wax deposits in oil/water stratified flow. The experiments are carried out in a state-of-the-art flow loop using a North Sea gas condensate and formation water. The flow map study using reflex came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…flow loop and found that the wax deposition rate in the oil/water two-phase flow was higher than that in single-phase flow. More recently, Hoffmann et al 35 performed two-phase, stratified oil/water flow-loop experiments and reported a higher deposit mass per unit area at a lower total flow rate. They also reported higher deposit thicknesses at higher water cuts and attributed this to a higher degree of gelation, resulting from decreased shear stress.…”
Section: ■ Introductionmentioning
confidence: 99%
“…flow loop and found that the wax deposition rate in the oil/water two-phase flow was higher than that in single-phase flow. More recently, Hoffmann et al 35 performed two-phase, stratified oil/water flow-loop experiments and reported a higher deposit mass per unit area at a lower total flow rate. They also reported higher deposit thicknesses at higher water cuts and attributed this to a higher degree of gelation, resulting from decreased shear stress.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the increase of deposit thickness with water cut further increasing has hardly been discussed in previous studies and neither has been the mechanism. As was mentioned in the study of Hoffmann, lower flow rate and higher water cut would contribute to the enhancement of gelation behavior in oil–water wax deposition.…”
Section: Resultsmentioning
confidence: 82%
“…[150] The presence of water in two-phase flows, as either water-in-oil or oil-in-water blend, has been reported to have inconclusive effects on wax deposition. While many studies have reported a decrease in wax deposition with increasing water fraction, [115,[150][151][152][153][154][155] others have reported an increase in wax deposition with increasing water fraction, [156,157] or no significant change due to the presence of water. [55,105] Clearly, more studies are needed to establish a conclusive effect of the presence of water on wax deposition.…”
Section: Water Droplets and Emulsionmentioning
confidence: 99%